Rasch calibration and optimal categorization of the sport fandom questionnaire. Issue 1 (17th May 2021) - Kim, Han Soo; Kang, Minsoo; Kim, Minjung
Abstract : Purpose: The purpose of this study is to evaluate the category function of the sport fandom questionnaire (SFQ), determine the optimal categorization of the SFQ and calibrate the measurement qualities of the newly modified rating scale option using Rasch analysis. Design/methodology/approach: This paper relies on the Rasch analysis to validate the SFQ. A series of studies are performed based on analysis procedures for the responses from 244 (study 1) and 477 (study 2) participants. Findings: The results revealed that the original SFQ consisting of the eight-category rating scale is flagged due to irregular observation distribution and disordering of thresholds, whereas both six-category and seven-category rating scales meet the guidelines for the optimal categorization. However, only the seven-category rating scale showed desirable model-data fit indices. Furthermore, the results of the Rasch calibration model showed that all items of the SFQ have large variability, and a person's ability level varied moderately along the continuum. Originality/value: Unlike previous studies, examining the psychometric properties of the SFQ, the current study provides information about the optimal categorization and presents a novel reconstruction category in measuring individuals' sport fandom level. In measuring the level of sport fandom, the authors suggest the use of a seven-category rating scale that the current study found to exhibit reliability and construct validity.